1999
DOI: 10.1016/s0969-2126(99)80020-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual conformations for the HIV-1 gp120 V3 loop in complexes with different neutralizing Fabs

Abstract: The V3 loop can adopt at least two different conformations for the highly conserved Gly-Pro-Gly-Arg sequence at the tip of the loop. Thus, the HIV-1 V3 loop has some inherent conformational flexibility that may relate to its biological function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
109
0
7

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 81 publications
12
109
0
7
Order By: Relevance
“…The flexibility conferred by this highly conserved glycine residue meets the requirements for permitting the spatial and temporal relationships of the C-terminal α-helix and the N-terminal loop. This finding is consistent with the generally accepted role of glycine in providing the freedom necessary for the regulation of both folding and function of a protein (22)(23)(24)(25)(26)(27)(28). In addition, it has been found experimentally that Gly 436 has a functional role in the entry process of the virus (6).…”
Section: Discussionsupporting
confidence: 89%
“…The flexibility conferred by this highly conserved glycine residue meets the requirements for permitting the spatial and temporal relationships of the C-terminal α-helix and the N-terminal loop. This finding is consistent with the generally accepted role of glycine in providing the freedom necessary for the regulation of both folding and function of a protein (22)(23)(24)(25)(26)(27)(28). In addition, it has been found experimentally that Gly 436 has a functional role in the entry process of the virus (6).…”
Section: Discussionsupporting
confidence: 89%
“…Crystal structure of activated Bax epitope FW Peyerl et al disallowed region (Table 1), which is a highly conserved g turn in most antibody structures. 22 The electron density omit map clearly defined the orientation and conformation of the Bax peptide in the 6A7 binding site (Figure 1c). The only peptide side chain residue with poorly defined electron density was solvent-exposed Q18.…”
Section: Resultsmentioning
confidence: 93%
“…Additionally, the structures of several neutralizing antibodies complexed with their V3 loop epitopes revealed that the V3 loop exists in at least two quite different conformation (48). This suggests that the V3 loop may adopt different structures, adding yet another layer of difficulty to its recognition by the immune system.…”
Section: Discussionmentioning
confidence: 99%